Individual and Combined Effects of Bacillus Thuringiensis and Azadirachtin on Plodia Interpunctella Hübner (Lepidoptera: Pyralidae). Issue 1 (25th August 2016) - Nouri-Ganbalani, Gadir; Borzoui, Ehsan; Abdolmaleki, Arman; Abedi, Zahra; George Kamita, Shizuo
Abstract: The Indianmeal moth, Plodia interpunctella Hübner (Lepidoptera: Pyralidae), is a major stored product pest that is found throughout the world. In this study, the effect of oral exposure to Bacillus thuringiensis (Berliner) subsp. kurstaki (Bacillales: Bacillaceae) and azadirachtin was evaluated in third instar P. interpunctella under laboratory conditions. The median lethal concentration (LC50 ) of Bt and azadirachtin on third instars was 490 and 241 μg a.i./ml, respectively. The median lethal time (LT50 ) of these insecticides was the same (4.5 d following exposure to 750 or 400 μg a.i./ml of Bt or azadirachtin, respectively). When the larvae fed on diet containing LC30 concentrations of both Bt and azadirachtin an additive interaction in terms of mortality was found. A synergistic interaction was found when the larvae fed on diet containing LC50 concentrations of both insecticides. Larvae that fed on insecticide-containing diet (either Bt or azadirachtin at an LC30 concentration, or both insecticides at LC30 or LC50 concentrations) showed lower glycogen and lipid levels, and generally lower protein content in comparison to control larvae. Larvae that fed on diet containing both Bt and azadirachtin showed reduced weight gain and nutritional indices in comparison to control larvae or larvae fed on the diet containing only one of the insecticides. Finally, exposure to both insecticides, either individually or in combination, reduced the level of digestive enzymes found in the midgut. Our findings indicate that both Bt and azadirachtin, either individually or in combination have significant potential for use in controlling of P. interpunctella .